Peripheral Neuropathy in Krabbe's Disease - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A 13-year-old female child presenting with scoliosis, pes cavus, distal lower extremity weakness, sensory loss, and delayed nerve conduction velocities, initially diagnosed as Charcot-Marie-Tooth disease, later developed lower extremity spasticity and laboratory evaluations were consistent with Krabbe's disease, in a report from the Alfred I duPont Institute, Wilmington, DE.